Digital Health Advocacy: Exploring Instagram's Role in Promoting Public Support for Sugar-Sweetened Beverage Excise - Anggraini, Maya; Septiani, Winda (The Indonesian Journal of Communication Studies, 2025)
The Instagram account @fyindonesians has emerged as a response to the rising consumption of Sugar-Sweetened Beverages (SSBs) in Indonesia and the lack of comprehensive regulatory instruments to address it. This study examines how @fyindonesians contributes to building public support for implementing an SSB tax as a health policy intervention. Using a qualitative case study design, the analysis is grounded in the Theory of Interactive Media Effects. Data were obtained through semi-structured interviews, complemented by content analysis via the Fanpage Karma application and validated through triangulation. The results indicate that @fyindonesians actively shapes social understanding of health issues through the platform's interactive affordances, utilizing both cue- and action-route mechanisms. The cue route directs initial audience attention through engaging visuals, social metrics, and consistent content style. In contrast, the action route fosters deeper cognitive engagement via interactive features, gradual information processing, and reflection on consumption behavior. These mechanisms jointly enhance user engagement, cultivate positive health attitudes, and encourage support for SSB excise.